The influence of history of anemia in pregnant women on the incident of stunting newborn - Heni Puji Wahyuningsih; Khadizah H. Abdul-Mukmin; Diani Fadmi Putri (Jurnal Kesehatan Ibu dan Anak, 2024)
Maternal and Child Health Problems (MCH) are still a health problem in Indonesia. Many factors affect the stunting condition, one of which is the history of anemia in pregnant women. The study aimed to know the effect of a history of anemia in pregnant women on stunting in newborns. The research design used case control. The population was all newborns of ??the Ponjong II Public Health Center (PHC) Gunungkidul working area in 2020-2022, with as many as 315 babies. The election of case and control groups used inclusion and exclusion criteria, which were selected from 62 samples. The research instrument used a table of data collection. Data analysis used univariate and odds ratio analysis, and Mantel Haenszel. The results of the study show that anemia in pregnancy influences stunting conditions in newborns. Mothers who have a history of anemic conditions during pregnancy and stunting conditions are 28,125 times more likely than mothers who have no history of anemia. There is an influence of anemia history in pregnant women that affects the stunting condition. A history of anemia increases the risk of newborn babies having stunts.